1973
DOI: 10.1139/v73-249
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Conformation of the Tetrahedral Intermediate in the Hydrolysis of Amides. Selective Cleavage of the Tetrahedral Intermediate Controlled by Orbital Orientation

Abstract: The basic hydrolysis of N-disubstituted imidate salts proceeds via a hemi-orthoamide tetrahedral intermediate which can in principle give amide-alcohol or ester-amine products. Experimental evidence has been obtained which shows that the specific conformation of the tetrahedral intermediate determines products formation and it is further suggested that theorientation ofthe lone pair orbitals of the heteroatoms governs this remarkable selective decomposition.L'hydrolyse basique des sels d'imidate N-disubstitues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
30
1
2

Year Published

1973
1973
2000
2000

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 4 publications
3
30
1
2
Order By: Relevance
“…Stereoelectronic cleavage of a tetrahedral intermediate is defined in the following way: specific cleavage of a carbon-oxygen or a carbon-nitrogen bond which occurs when two heteroatoms (oxygen or nitrogen) of the tetrahedral intermediate each have an orbital oriented antiperiplanar to the departing 0-alkyl or Nalkyl leaving group. ' We have reported a study of the basic hydrolysis of several imidate salts having either a syn or an anti conformation (2,3). The stereoelectronic 'Theoretical calculations have been carried out and support this theory (5).…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Stereoelectronic cleavage of a tetrahedral intermediate is defined in the following way: specific cleavage of a carbon-oxygen or a carbon-nitrogen bond which occurs when two heteroatoms (oxygen or nitrogen) of the tetrahedral intermediate each have an orbital oriented antiperiplanar to the departing 0-alkyl or Nalkyl leaving group. ' We have reported a study of the basic hydrolysis of several imidate salts having either a syn or an anti conformation (2,3). The stereoelectronic 'Theoretical calculations have been carried out and support this theory (5).…”
mentioning
confidence: 94%
“…We have described recently a new theory of stereoelectronic control for the cleavage of tetrahedral intermediates which are formed during the hydrolysis of esters (I), and amides (2)(3)(4). In this new theory, the precise conformation of the tetrahedral intermediate (hemiorthoester or hemiorthoamide) plays a major role in determining the products formed.…”
mentioning
confidence: 99%
“…It was also observed that the fragmentation of the resulting tetrahedral hydrotrioxide intermediates is also conformation dependent and the results could also be rationalized on the basis of stereoelectronic effects. Further studies (9,10) on the stereocontrolled fragmentation of various tetrahedral intermediates were carried out in our laboratory and this work led us to propose a new general theory for the understanding of hydrolytic processes, which is primarily based on stereoelectronic principles (1 1-13). Consequently, this completely unexpected annoying result led to the discovery of a rather fruitful event!…”
Section: Introductionmentioning
confidence: 99%
“…'Undergraduate summer student, 1977. 3Revision received June 6, 1979. control of reactivity was later extended to the breakdown of tetrahedral intermediates formed during the hydrolysis of orthoesters (3,4), imidate salts (3,5), esters, and amides (3,6). In view of the fact that stereoelectronic control of reactivity may be important in many other reactions (3), including reaction of phosphate diesters (7), and reactions of biological interest (S), it seemed important to investigate further the mechanism of oxidation of acetals by ozone.…”
mentioning
confidence: 99%